Fuzzy Binomial Option pricing model: a comparison of the fuzzy binomials and modified numerical methods - Kanthamanond, Piti (2009)
The fuzzy set concept can be applied to the derivative pricing model to cover the uncertainty in the market. The aim of this study is to modify existing fuzzy binomial option pricing models and tests them with several lattice numerical methods to compare the performance and clarify the benefit and necessity of the fuzzy models over the non-fuzzy models. The empirical validation of these models on the artificial data and on the S&P 100 index options is provided with the various tests which cover details in both effectiveness (precision) and efficiency (cost and accuracy).